An elemental exploration of the metal contents of an early 13th-century craft box from Lõhavere, using pXRF - Esmee Jorinde Hummel; Marcus Adrian Roxburgh; Hans D. J. Huisman (Eesti Arheoloogiaajakiri, 2024)
The craft box recovered from a 13thÂcentury hillfort at LÃµhavere, Estonia, contained a well-preserved selection of copperÂalloy objects. The limited corrosion on these objects allowed a more accurate estimation of their compositions through nonÂdestructive surface measurements. Using the resulting pXRF database, this study explored a possible correlation between the types of objects and their material composition. By comparing the most common contaminants with the alloying metals, a qualitative estimation of the material quality was conducted. The results showed that despite a considerable overlap between object types, the material composition dif fered based on the itemsâ appearance and function. A shift from brass to bronze and tinned objects coincided with a greater availability of tin at the hillfort, as well as a rise in silver smith ing. Moreover, objects with a silver appearance seemed to be more desirable in this period, apart from some highÂstatus personal ornaments and traditional spiral tube decorations. The results possibly reflect different metalworking practices compared to earlier periods and contemporary sites. Some evidence of recycling is present among the spiral tubes, suggesting that they originated from different raw material sources, possibly removed from obsolete clothing. Alternatively, this could indicate a varying quality of imported copperÂalloy, including wire, along the Hansa trade routes.